2018
DOI: 10.1038/s41564-018-0205-8
|View full text |Cite
|
Sign up to set email alerts
|

Anthropogenic and environmental factors associated with high incidence of mcr-1 carriage in humans across China

Abstract: MCR-1-positve Escherichia coli (MCRPEC) have been reported in humans worldwide; however, thus far, their prevalence is low and potential sources for human mcr-1 carriage have not yet been identified. Here, we analyse a nationwide epidemiological dataset on MCRPEC in humans throughout China and assess the factors associated with MCRPEC carriage using natural and national anthropogenic data. We identified 774 non-duplicate MCRPEC isolates from 774 stool samples collected from 5,159 healthy individuals in 30 prov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
120
1
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 146 publications
(130 citation statements)
references
References 32 publications
6
120
1
3
Order By: Relevance
“…The high diversity of the mcr-1-positive E. coli and K. pneumoniae isolates detected in the present study corresponds to the results for mcr-positive Enterobacteriaceae isolated from different sources (food, animals, and humans) in other studies (Zurfluh et al, 2016;Luo et al, 2017;Roschanski et al, 2017;Zurfluh et al, 2017;El Garch et al, 2018). However, some studies have described an increased prevalence of E. coli with mcr-1 belonging to ST10 obtained from food animals, food, and humans (Zurfluh et al, 2016;El Garch et al, 2018;Shen et al, 2018;Wu et al, 2018). Similarly, E. coli isolates found here belonging to ST10 (n = 5) and ST744 (n = 5) were most often detected.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The high diversity of the mcr-1-positive E. coli and K. pneumoniae isolates detected in the present study corresponds to the results for mcr-positive Enterobacteriaceae isolated from different sources (food, animals, and humans) in other studies (Zurfluh et al, 2016;Luo et al, 2017;Roschanski et al, 2017;Zurfluh et al, 2017;El Garch et al, 2018). However, some studies have described an increased prevalence of E. coli with mcr-1 belonging to ST10 obtained from food animals, food, and humans (Zurfluh et al, 2016;El Garch et al, 2018;Shen et al, 2018;Wu et al, 2018). Similarly, E. coli isolates found here belonging to ST10 (n = 5) and ST744 (n = 5) were most often detected.…”
Section: Discussionsupporting
confidence: 89%
“…The most common type of plasmid was IncX4, which carried the mcr-1 gene in 77% (44/57) of E. coli and K. pneumoniae isolates from turkey meat and liver samples (n = 16) from the Czechia, Germany, Poland, and Brazil. IncX4 plasmids carrying mcr-1 have also been described in E. coli isolated from meat and humans in China Luo et al, 2017;Shen et al, 2018), chicken meat from Brazil (Monte et al, 2017), chicken and turkey meat from the EU (Hasman et al, 2015;Alba et al, 2018), and pigs in Germany (Roschanski et al, 2017). The conjugation assay showed that the majority of IncX4 plasmids carrying mcr-1 were transferable to recipient E. coli cells (14/17).…”
Section: Discussionmentioning
confidence: 99%
“…Abuse of the colistin in animal production is believed to drive the selective pressure for the emergence and transmission of mcr‐1 . Moreover, animal products and farming environment are suspected to be important routes to spread the mcr‐1 gene to human beings (Liu et al, ; Shen, Zhou, et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…The emergence of the colistin‐resistant Enterobacteriaceae , such as MCRPEC, deteriorates the situation in the face the public medical “post‐antibiotic era” (Shen, Zhou, et al, ). Epidemiology research of mcr‐1 ‐positive Enterobacteriacea raises serious concerns about the increasing risk to severe humans infections by PDR Gram‐negative pathogens.…”
Section: Introductionmentioning
confidence: 99%
“…Since the mcr-1 gene was reported, many studies clearly clarified the status quo of its transmission and provided its epidemic evidence in food, livestock and human [1618]. How to effectively avoid the public health hazards induced by mcr-1 has become an important challenge.…”
Section: Introductionmentioning
confidence: 99%